Sexually transmitted pathogens causing urethritis: A mini-review and proposal of a clinically based diagnostic and therapeutic algorithm - Sadoghi, Birgit; Kränke, Birger; Komericki, Peter; Hutterer, Georg (Frontiers in Medicine, 2022)
The purpose of this mini review is to provide the latest information and concepts on diagnosis and treatment of the the most common sexually transmitted pathogens causing urethritis. The incidence of several sexually transmitted infections that cause urethritis is increasing, and this genitourinary syndrome is among the most common reason young men see clinical care. The authors performed a literature search including the currently valid guidelines, and an overview of the most relevant pathogens is given. Moreover, the authors developed a clinically applicable diagnostic and therapeutic algorithm, since early diagnosis and correct treatment can sometimes prevent infected individuals from significant morbidity. Future research will focus on new methods to combat pathogens that cause urethritis, including vaccination.